2019
DOI: 10.5114/aoms.2019.86648
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CYP3A4 is associated with poor response to ifosfamide treatment in children with solid embryonic tumors

Abstract: Introduction: The CYP450 complex participates in the metabolism of ifosfamide, an antineoplastic drug used to treat solid tumors. genes contain several single nucleotide polymorphisms (SNPs) that confer different activity towards the enzyme. The aim of our study was to analyze gene frequencies of allelic variants and their association with ifosfamide blood levels and patient prognosis. Material and methods: 148 DNA samples from children were analyzed. Genotyping was performed by real-time PCR with TaqMan probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The functional significance of the rs2740574 variant in CYP3A4 suggests that CYP3A4*1B does not affect the metabolism and elimination of CYP3A4 substrates, [13][14][15][16][17][18] but the rs2740574 variant has been found to be associated with high levels of ifosfamide and a worse therapeutic response in children with solid embryonal tumours. 19 Regarding the role of this variant in the pharmacokinetic parameters of midazolam, a clear association between the parameters and the variant in CYP3A4 has also not been found, 18,20,21 and similar results were observed in this cohort of critically ill patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The functional significance of the rs2740574 variant in CYP3A4 suggests that CYP3A4*1B does not affect the metabolism and elimination of CYP3A4 substrates, [13][14][15][16][17][18] but the rs2740574 variant has been found to be associated with high levels of ifosfamide and a worse therapeutic response in children with solid embryonal tumours. 19 Regarding the role of this variant in the pharmacokinetic parameters of midazolam, a clear association between the parameters and the variant in CYP3A4 has also not been found, 18,20,21 and similar results were observed in this cohort of critically ill patients.…”
Section: Discussionsupporting
confidence: 58%
“…Studies in the literature have shown that wide variation in the expression and activity of CYP3A isoforms in humans, which is reflected in large inter‐individual differences in the metabolism and clearance of CYP3A substrates such as midazolam. The functional significance of the rs2740574 variant in CYP3A4 suggests that CYP3A4*1B does not affect the metabolism and elimination of CYP3A4 substrates, 13‐18 but the rs2740574 variant has been found to be associated with high levels of ifosfamide and a worse therapeutic response in children with solid embryonal tumours 19 …”
Section: Discussionmentioning
confidence: 99%
“…A prostate cancer prevention trial revealed that finasteride, an anticancer drug, showed altered concentrations due to the CYP3A4*1G polymorphism [ 74 ]. A recent study on ifosfamide treatment in children with solid embryonic tumors identified associations of drug treatment among CYP polymorph individuals, and found that detrimental therapeutic failure was associated with the rs2740574 polymorphism in CYP3A4 [ 108 ]. As CYP3A4 is not merely involved in vitamin D metabolism, its involvement in other aspects (including drug metabolism) needs to be meticulously examined to improve pharmacotherapy.…”
Section: Cyp3a4 Polymorphisms In Various Pat H ...mentioning
confidence: 99%
“…Although it has been proposed that sex differences in the activity of CYP3A4 exist [ 14 , 15 ], current evidence supporting this is limited, non-existent [ 16 ], or contradictory [ 17 ]. In previous studies of our group, the allelic variants of the CYP450 genes (nine probes in the CYP2B6, CYP2C9, CYP3A4, and CYP3A5 genes) have been analyzed, and an association of toxicity and response to treatment was reported in patients with solid tumors with the allelic CYP3A4 and CYP3A5 variants [ 18 , 19 ], so it was decided to explore them in a cohort of critically ill pediatric patients. Due to the reasons stated before, the aim of the present study was to determine the sex and age influence on association of CYP450 polymorphism with midazolam levels in critically ill children.…”
Section: Introductionmentioning
confidence: 99%